The Influence of The Problem-Based Learning with Radical Constructivism Module on Students' Problem-Solving Skills - Ulhaq*, Riza; Huda, Ismul; Rahmatan, Hafnati; Fathiya, Nir; Chan, Kristina Merencillo (Jurnal Pendidikan Sains Indonesia, 2024)
Problem solving skills (PSS) are one of the high-level thinking skills that must be possessed by students. This skill will help students apply scientific content to solve problems in real life. The purpose of this study was to determine the effect of problem based learning (PBL) models with a radical construktivism module on PSS. Data were collected in February to March 2022. The method in this study used an experimental method with nonrandomized post test only control-group design. This research was conducted in two classes: the experimental class using PBL model learning with radical constructivism module and the control class that only using PBL model learning. The samples were 160 students. The instrument was tests to assess PSS. Data analysis used independent sample t-test to determine effect of PBL model learning with radical constructivism module on PSS. T-test results showed that value sig 0,05. The result showed that students who received PBL model learning and the radical constructivism module obtained significantly better PSS compared to students who only received PBL model learning